Analysis and Control of Bankruptcy and Reorganization Processes: Case Studies Using Accounting Data - George Abuselidze; Anna Slobodianyk (E3S Web of Conferences, 2020)
The article is devoted to the justification and development of recommendations for improving the use of accounting data for the analysis and control of bankruptcy and reorganization processes of enterprises. It is determined that in conditions of financial and political instability, the activities of enterprises are accompanied by crisis situations, which may result in insolvency or bankruptcy. The peculiarities of processes of bankruptcy and reorganization of enterprises, using the methods of economic analysis, analysis of financial state and efficiency of the investigated company, as well as evaluated the effectiveness of the use of accounting data for analysis and control of processes of bankruptcy and reorganization of enterprises. Overview of cases in business practice for which the company is liquidated. The state and volume of activity of the basic enterprise in the context of the main indicators of financial statements for the last three years are analyzed. As a result of the analysis of the enterprise, it is proved that LLC Agrocomplex is profitable, with positive growth trends for most of the main indicators of economic activity. To identify signs of a crisis, the company assessed the threat of bankruptcy based on rapid diagnostics. The authors proved that the twofactor model for assessing the probability of bankruptcy of an enterprise shows that the probability of bankruptcy for LLC Agrocomplex is very low. The authors prove that when analysing the financial condition of an enterprise, a situation may arise when some indicators of the discriminant model for a particular enterprise may be very low compared to their "normal" values, and others - on the contrary, too high, which is also "bad". It is proved that their combination can indicate a stable financial condition of the enterprise, since it is the calculation of one integral indicator based on all input factors at the same time.
Keywords: 330